2020
DOI: 10.1021/acs.inorgchem.0c01520
|View full text |Cite
|
Sign up to set email alerts
|

Copper Bis(thiosemicarbazonato)-stilbenyl Complexes That Bind to Amyloid-β Plaques

Abstract: Alzheimer’s disease is characterized by the presence of extracellular amyloid-β plaques. Positron emission tomography (PET) imaging with tracers radiolabeled with positron-emitting radionuclides that bind to amyloid-β plaques can assist in the diagnosis of Alzheimer’s disease. With the goal of designing new imaging agents radiolabeled with positron-emitting copper-64 radionuclides that bind to amyloid-β plaques, a family of bis­(thiosemicarbazone) ligands with appended substituted stilbenyl functional groups h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
24
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(26 citation statements)
references
References 64 publications
0
24
0
Order By: Relevance
“…Several studies have reported that Aβ-targeting bifunctional chelators can be utilized as potential 64 Cu PET imaging agents for AD. With the introduction of the hydrophilic metal-chelating azamacrocycle, the developed amphiphilic compound LS-4 could serve as a bifunctional chelator. Given the promising results from the ex vivo studies using the nonradioactive Cu-LS-4 complex, we set out to explore whether the radioactive 64 Cu-LS-4 complex could be used as a potential PET imaging agent for AD.…”
Section: Results and Discussionmentioning
confidence: 99%
“…Several studies have reported that Aβ-targeting bifunctional chelators can be utilized as potential 64 Cu PET imaging agents for AD. With the introduction of the hydrophilic metal-chelating azamacrocycle, the developed amphiphilic compound LS-4 could serve as a bifunctional chelator. Given the promising results from the ex vivo studies using the nonradioactive Cu-LS-4 complex, we set out to explore whether the radioactive 64 Cu-LS-4 complex could be used as a potential PET imaging agent for AD.…”
Section: Results and Discussionmentioning
confidence: 99%
“…Numerous studies have reported that Aβ-targeting bifunctional chelators can be utilized as potential 64 Cu PET imaging agents for AD. [85][86][87][88][89] With the introduction of the hydrophilic metalchelating azamacrocycle, the developed amphiphilic compound LS-4 could serve as a bifunctional chelator. Given the promising results from the ex vivo studies using the non-radioactive Cu-LS-4 complex, we set out to explore whether the radioactive 64 Cu-LS-4 complex could be used as a potential PET imaging agent for AD.…”
Section: Logd Determination Of the 64 Cu-ls-4 Complexmentioning
confidence: 99%
“…Numerous studies have reported that Aβ-targeting bifunctional chelators can be utilized as potential 64 Cu PET imaging agents for AD. [85][86][87][88][89] With the introduction of the hydrophilic metalchelating azamacrocycle, the developed amphiphilic compound LS-4 could serve as a bifunctional chelator. Given the promising results from the ex vivo studies using the non-radioactive Cu-LS-4 complex, we set out to explore whether the radioactive 64 Cu-LS-4 complex could be used as a potential PET imaging agent for AD.…”
Section: Logd Determination Of the 64 Cu-ls-4 Complexmentioning
confidence: 99%